THE EFFECT OF PRICE, SERVICE, PROMOTION, AND LOCATION ON THE INTEREST OF GROOMING CAT IN PET SHOP PANGKALPINANG - Juhari Juhari; Yulia Fitriani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze the effect of price, service, promotion, and location on interest in cat grooming in theNagasatwaPet Shop Pangkal Pinang. The population in this study were consumers who had groomed at the Nagasatwa Pet Shop in Pangkalpinang. The sample was determined using a qualitative method through a descriptive approach as many as 352 respondents. Researchers used interviews, direct observation, and supporting documents needed to collect data during the study. The data analysis technique used is multiple linear regression analysis model, coefficient of determination test (R2), F test (simultaneous), and t test (partial). Based on this study, it was found that the variables of price, service, promotion, and location had a significant effect on the interest in grooming cats in the Nagasatwa Pet Shop Pangkalpinang. It can be seen from the results of the F test calculation that F count (11.928) > from F table (5.32) while the significance. Keywords: Price, Service, Promotion, Location, Cats Grooming, Pet Shop